Hubungan Kadar Sebum pada Penderita Akne Vulgaris di SMAN 75 Jakarta Utara - Arni Ismi Fadhila; Sukmawati Tansil Tan (Universitas Malahayati Lampung, 2024)
ABSTRACT Acne Vulgaris (AV) is a chronic inflammatory skin disease affecting the pilosebaceous glands. Acne Vulgaris commonly occurs in adolescents due to hormonal fluctuations that stimulate the sebaceous glands to produce more sebum. The face, back, chest, and shoulder areas often display a predilection for AV. The aim of this study is to assess the facial sebum levels of students at SMAN 75 North Jakarta predisposed to acne vulgaris. This study used a cross-sectional design and was conducted at SMAN 75 North Jakarta in January 2024. Sampling was carried out using non-random consecutive sampling. Data obtained from the samples will be processed and analyzed using SPSS 22.0. Sebum levels were measured using a skin analyzer SK-08 on the left and right sides of the face. The characteristics of the AV group in students of SMAN 75 North Jakarta showed severe acne as many as 37 people (8.20%), moderate acne as many as 100 people (6.57%), and mild acne as many as 33 people (5.75%). Based on the Kruskal-Wallis statistical test, there was a significant difference in the average oil content between the three acne severity groups (P-value 0.001). These results indicate that increased sebum levels are associated with increased severity of acne vulgaris. Keywords: Acne Vulgaris, Sebum Levels, Pilosebasea Glands, Skin Analyzer ABSTRAK Akne Vulgaris (AV) adalah penyakit kulit inflamasi kronis yang menyerang kelenjar pilosebasea. Akne Vulgaris umumnya terjadi pada remaja akibat fluktuasi hormonal yang merangsang kelenjar sebasea untuk memproduksi lebih banyak sebum. Area wajah, punggung, dada, dan bahu sering menunjukkan kecenderungan AV. Tujuan dari penelitian ini adalah untuk menilai kadar sebum wajah siswa di SMAN 75 Jakarta Utara yang rentan terhadap akne vulgaris. Penelitian ini menggunakan desain cross-sectional dan dilakukan di SMAN 75 Jakarta Utara pada bulan Januari 2024. Pengambilan sampel dilakukan dengan menggunakan non-random sequential sampling. Data yang diperoleh dari sampel akan diolah dan dianalisis menggunakan SPSS 22.0. Kadar sebum diukur menggunakan skin analyzer SK-08 pada sisi kiri dan kanan wajah. Karakteristik kelompok AV pada siswa/i SMAN 75 Jakarta Utara menunjukkan Akne berat sebanyak 37 orang (8,20%), akne sedang sebanyak 100 orang (6,57%), dan akne ringan sebanyak 33 orang (5,75%). Berdasarkan uji statistik Kruskal-Wallis, terdapat perbedaan signifikan rata-rata kadar minyak di antara ketiga kelompok tingkat keparahan akne (P-value 0,001). Hasil ini menunjukkan bahwa peningkatan kadar sebum berhubungan dengan peningkatan keparahan akne vulgaris. Kata Kunci: Akne Vulgaris, Kadar Sebum, Kelenjar Pilosebasea, Skin Analyzer